PENGARUH CORPORATE GOVERNANCE TERHADAP FIRM VALUE MELALUI INTELLECTUAL CAPITAL DISCLOSURE SEBAGAI VARIABEL MEDIASI - Rina Pricelya Ibrahim; Saarce Elsye Hatane (Business Accounting Review, 2017)
This study aimed to examine the influence of corporate governance on firm value through intellectual capital disclosure as mediating variable. This study also examined the indirect influence of corporate governance on firm value through intellectual capital disclosure as mediating variable. Data were obtained from 72 manufacture companies listed in Indonesia Stock Exchange from 2010-2015. Data were collected from annual reports and financial reports and processed by using WarpPLS software version 5.0. This study used a quantitative approach where the data obtained from company’s financial statement of 2010-2015. The data then processed by using PLS software. The result showed that there was negative and significant influence of corporate governance toward firm value, negative and significant influence of corporate governance toward firm value, and positive and significant influence of firm value and intellectual capital disclosure. The intellectual capital disclosure was successful in mediating the indirect influence of corporate governance and firm value.